Progress and Roadmap for Intelligent Self‐Healing Materials in Autonomous Robotics. Issue 19 (21st December 2020) - Tan, Yu Jun; Susanto, Glenys Jocelin; Anwar Ali, Hashina Parveen; Tee, Benjamin C. K.
Abstract: Robots are increasingly assisting humans in performing various tasks. Like special agents with elite skills, they can venture to distant locations and adverse environments, such as the deep sea and outer space. Micro/nanobots can also act as intrabody agents for healthcare applications. Self‐healing materials that can autonomously perform repair functions are useful to address the unpredictability of the environment and the increasing drive toward the autonomous operation. Having self‐healable robotic materials can potentially reduce costs, electronic wastes, and improve a robot endowed with such materials longevity. This review aims to serve as a roadmap driven by past advances and inspire future cross‐disciplinary research in robotic materials and electronics. By first charting the history of self‐healing materials, new avenues are provided to classify the various self‐healing materials proposed over several decades. The materials and strategies for self‐healing in robotics and stretchable electronics are also reviewed and discussed. It is believed that this article encourages further innovation in this exciting and emerging branch in robotics interfacing with material science and electronics. Abstract : Self‐healing materials are exciting avenues toward sustainable and intelligent long lifespan robots. The history and recent advances in material strategies for self‐healing in robotics and stretchable electronics toward future development of the fully autonomous self‐healing robots are reviewed.